Cumulative impacts across Australia's Great Barrier Reef: a mechanistic evaluation. Issue 1 (28th December 2021) - Bozec, Yves‐Marie; Hock, Karlo; Mason, Robert A. B.; Baird, Mark E.; Castro‐Sanguino, Carolina; Condie, Scott A.; Puotinen, Marji; Thompson, Angus; Mumby, Peter J.
Abstract: Cumulative impacts assessments on marine ecosystems have been hindered by the difficulty of collecting environmental data and identifying drivers of community dynamics beyond local scales. On coral reefs, an additional challenge is to disentangle the relative influence of multiple drivers that operate at different stages of coral ontogeny. We integrated coral life history, population dynamics, and spatially explicit environmental drivers to assess the relative and cumulative impacts of multiple stressors across 2, 300 km of the world's largest coral reef ecosystem, Australia's Great Barrier Reef (GBR). Using literature data, we characterized relationships between coral life history processes (reproduction, larval dispersal, recruitment, growth, and mortality) and environmental variables. We then simulated coral demographics and stressor impacts at the organism (coral colony) level on >3, 800 individual reefs linked by larval connectivity and exposed to temporally and spatially realistic regimes of acute (crown‐of‐thorns starfish outbreaks, cyclones, and mass coral bleaching) and chronic (water‐quality) stressors. Model simulations produced a credible reconstruction of recent (2008–2020) coral trajectories consistent with monitoring observations, while estimating the impacts of each stressor at reef and regional scales. Overall, simulated coral populations declined by one‐third across the GBR, from an average of 29% to 19% hard coral cover. By 2020, <20% of the GBR had coral cover higher than 30%, a status of reef health corroborated by scarce and sparsely distributed monitoring data. Reef‐wide annual rates of coral mortality were driven by bleaching (48%) ahead of cyclones (41%) and starfish predation (11%). Beyond the reconstructed status and trends, the model enabled the emergence of complex interactions that compound the effects of multiple stressors while promoting a mechanistic understanding of coral cover dynamics. Drivers of coral cover growth were identified; notably, water quality (suspended sediments) was estimated to delay recovery for at least 25% of inshore reefs. Standardized rates of coral loss and recovery allowed the integration of all cumulative impacts to determine the equilibrium cover for each reef. This metric, combined with maps of impacts, recovery potential, water‐quality thresholds, and reef state metrics, facilitates strategic spatial planning and resilience‐based management across the GBR.